The Assessment of Difference in Achievement Motivation Among Intercollegiate Players and Interuniversity Player (International Journal of Food and Nutritional Sciences, 2022)
To assess the difference in achievement motivation between the players of inter college and inter university level. A total sample of 320 subjects would be selected randomly. The sample would be subjected to the systematic purposive Sampling Technique. All the socio-demographic variables would be considered. Intercollegiate Players and Interuniversity Players for Achievement motivation variable, which shows that the mean and S.D. values of the Intercollegiate Players and Interuniversity Players were found to be 27.51±3.33 and 28.54±3.87 and S.E.M values of the Intercollegiate Players and Interuniversity Players were found to be 0.26 and 0.30 respectively. The Intercollegiate Players and Interuniversity Players had moderate achievement motivation but the Interuniversity players were significantly higher achievement motivation than the intercollegiate players. There was significant difference in achievement motivation between Intercollegiate Players and Interuniversity Players.